Advances in Bioengineering 2002
DOI: 10.1115/imece2002-32326
|View full text |Cite
|
Sign up to set email alerts
|

Flow-Induced Wall Pressure Under Average Resting Hemodynamic Conditions for Patient-Specific Abdominal Aortic Aneurysms

Abstract: Abdominal Aortic Aneurysms (AAAs) are characterized by a continuous dilation of the infrarenal segment of the abdominal aorta. Despite significant improvements in surgical procedures and imaging techniques, the mortality and morbidity rates associated with untreated ruptured AAAs are still outrageously high. AAA disease is a health risk of significant importance since this kind of aneurysm is mostly asymptomatic until its rupture, which is frequently a lethal event with an overall mortality rate in the 80% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Taylor and Yamaguchi have shown in ideal rigid wall models that the vortices at the distal end of the AAA models caused regions of high pressure [ 19 ]. However, Finol et al found in two patient-specific AAA models that hemodynamic pressure variation is insignificant along the inner AAA wall at any stage of the cardiac cycle and that its magnitude and distribution are dependent on the shape and size of an aneurysm [ 20 ]. Finol et al, in a later study, compared FSI and structural static simulations on idealised models in order to determine the best suited method to calculate AAA wall stresses [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Taylor and Yamaguchi have shown in ideal rigid wall models that the vortices at the distal end of the AAA models caused regions of high pressure [ 19 ]. However, Finol et al found in two patient-specific AAA models that hemodynamic pressure variation is insignificant along the inner AAA wall at any stage of the cardiac cycle and that its magnitude and distribution are dependent on the shape and size of an aneurysm [ 20 ]. Finol et al, in a later study, compared FSI and structural static simulations on idealised models in order to determine the best suited method to calculate AAA wall stresses [ 21 ].…”
Section: Introductionmentioning
confidence: 99%